Indication for Venovenous Extracorporeal Membrane Oxygenation: Is 65 Years Old, Too Old?. Issue 1 (19th October 2020) - Giani, Marco; Forlini, Clarissa; Fumagalli, Benedetta; Rona, Roberto; Pesenti, Antonio; Foti, Giuseppe
Abstract : Supplemental Digital Content is available in the text.